2018
DOI: 10.1016/j.toxrep.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and removal of anthracene and lead by a B. subtilis-produced biosurfactant

Abstract: HighlightsBacillus subtilis is able to produce a biosurfactant.B. subtilis could consume anthracene as a sole source of carbon.High amount of anthracene (%69.95) was degraded and removed in a solution inoculated with B. subtilis.High amount of lead (%82) was removed in a solution inoculated with B. subtilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The phylogenetic analysis revealed that the CYA20 and CYA27 strains had a 100% sequence similarity (Figure 1) to Acinetobacter baumannii (accession KF498713.1) and Bacillus subtilis (accession AY162130.1). These bacteria commonly correspond to a bacterial group known for crude oil hydrocarbons degradation capability in the sea and mangroves, such as Bacillus, Acinetobacter, Pseudomonas, and Rhodococcus (Chen et al 2020;Kim et al 2019;Syakti et al 2013;Salamat et al 2018). Tan et al (2018) and Sakthipriya et al (2015) reported that A. baumannii and B. subtilis were marine bacteria capable of degrading crude oil pollutants.…”
Section: Utilization Of Hydrocarbon Substrates and Production Of Bios...mentioning
confidence: 99%
“…The phylogenetic analysis revealed that the CYA20 and CYA27 strains had a 100% sequence similarity (Figure 1) to Acinetobacter baumannii (accession KF498713.1) and Bacillus subtilis (accession AY162130.1). These bacteria commonly correspond to a bacterial group known for crude oil hydrocarbons degradation capability in the sea and mangroves, such as Bacillus, Acinetobacter, Pseudomonas, and Rhodococcus (Chen et al 2020;Kim et al 2019;Syakti et al 2013;Salamat et al 2018). Tan et al (2018) and Sakthipriya et al (2015) reported that A. baumannii and B. subtilis were marine bacteria capable of degrading crude oil pollutants.…”
Section: Utilization Of Hydrocarbon Substrates and Production Of Bios...mentioning
confidence: 99%
“…In the available literature there are some references to a combined environmental pollution with lead and some PAHs (e.g., [ 24 ]). However, the binary combined effects of B(a)P and lead on the organism have not been the focus of direct studies in the previous works of ours or of anyone else judging by the literature known to us.…”
Section: Introductionmentioning
confidence: 99%